PENGARUH MODEL NUMBER HEAD TOGETHER TERHADAP KETERAMPILAN MENULIS BAHASA INDONESIA KELAS V DI SDN 04 NGELING JEPARA - Afina Rikhanatus Sufa; Muh. Muhaimin; Muhammad Misbahul Munir (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study investigates the impact of implementing the Numbered Heads Together (NHT) cooperative learning model on Indonesian writing competence in fifth-grade students at SDN 04 Ngeling Jepara, who previously demonstrated low proficiency. This study adopts a pre-experimental approach with a One-Group Pre-test – Post-test design. The research participants include the entire fifth-grade population of 29 students, selected using a saturated sampling technique. Data on writing ability were obtained through pre- and post-tests, which were then statistically analysed using a paired t-test. The analysis results showed substantial progress, with the average writing ability score increasing from 49.3 in the pre-test to 82.5 in the post-test. The t-test yielded a significance value of 0.000 (p 0.05), confirming the strong impact of the intervention. The effectiveness level of this model was categorised as moderate, with an N-Gain score of 0.67. Thus, it can be concluded that the implementation of the NHT model significantly and effectively contributed to the improvement of students' writing skills.